2022
DOI: 10.3390/agriculture12111873
|View full text |Cite
|
Sign up to set email alerts
|

N Addition Mitigates Water Stress via Different Photosynthesis and Water Traits for Three Native Plant Species in the Qinghai–Tibet Plateau

Abstract: Reseeding with native plants to rebuild alpine meadow has become a popular way of ecological restoration. However, the harsh environment poses a great challenge to the establishment of native plants due to poor management of water and nutrients. How water–fertilizer interaction influences dominant grass species is still unclear, and reasonable water and fertilizer conditions are still not determined. Our results showed that addition of nitrogen could mitigate the photosynthetic and water-use traits caused by w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 50 publications
0
1
0
Order By: Relevance
“…The underground agronomic efficiency of nitrogen in F. coelestis under W H and W M increased with increasing fertility. The underground agronomic efficiencies of nitrogen in F. coelestis under W H F L , W M F L , and W M F M were negative, similar to the findings of Brown et al (2019) and consistent with the change law of underground biomass [40]. When there is sufficient water, along with an increase in nitrogen fertilizer, the dissolution and transport rates of soil nutrients are high; therefore, the available nitrogen content, urease activity of urease, root respiration, and nutrient absorption are adequate.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The underground agronomic efficiency of nitrogen in F. coelestis under W H and W M increased with increasing fertility. The underground agronomic efficiencies of nitrogen in F. coelestis under W H F L , W M F L , and W M F M were negative, similar to the findings of Brown et al (2019) and consistent with the change law of underground biomass [40]. When there is sufficient water, along with an increase in nitrogen fertilizer, the dissolution and transport rates of soil nutrients are high; therefore, the available nitrogen content, urease activity of urease, root respiration, and nutrient absorption are adequate.…”
Section: Discussionsupporting
confidence: 89%
“…This conclusion was verified via SEM, which revealed that available N (0.821) and N (0.244) had positive effects on NUE, whereas water had an indirect effect on NUE through available N (0.437). Specifically, the aboveground agronomic efficiency of nitrogen in F. coelestis decreased with an increase in water stress and fertility, similar to the results of Rietra et al (2017) and consistent with the change law of aboveground biomass [40]. This may be because the addition of appropriate nitrogen can increase the soil nitrogen content, whereas sufficient water can promote the dissolution and transport of available nitrogen, improve urease activity, provide sufficient nitrogen to plants, and promote plant growth.…”
Section: Discussionsupporting
confidence: 80%
“…This suggests that water is a key limiting factor for the N fertiliser utilisation efficiency of these plants, although it does not directly affect it. Under different water treatments, both the N fertiliser utilisation efficiency and the biomass of the aboveground parts of P. crymophila and S. purpurea showed a decreasing trend when fertilisation increased [45]. This indicates that when the N supply is sufficient, these plants tend to allocate more N to the underground parts, possibly to ensure their survival in the extreme environment of the Qinghai-Tibet Plateau, and thus adopting a survival strategy that prioritises supplying the underground parts [46].…”
Section: Impacts Of Different Water and Fertiliser Conditions On Nitr...mentioning
confidence: 98%